Women's Leadership And Banking Productivity: Mediating Role Of Artificial Intelligence - Data, Muhammad Umar; Halim, Firmansyah; Amanda, Alya Dhea (LPPM ISNJ Bengkalis, 2024)
This study aims to analyze the influence of women's leadership on banking productivity with artificial intelligence (AI) as a mediator. This study involved 90 employees of Bank SulSelBar Makassar, where the entire population was sampled (saturated sample). The method used is quantitative, using primary data collected through questionnaires. The data analysis technique used structural equation modeling (SEM) to evaluate the relationship between variables with the help of SmartPLS software version 3.0. The study results indicate that women's leadership positively affects banking productivity and the implementation of AI. However, the implementation of AI itself does not affect banking productivity. AI cannot mediate the influence of women's leadership on banking productivity. This study advises banks to continue supporting inclusive women's leadership and adopt advanced technology to increase productivity. Theoretically, this study does not support the assumption that technology such as AI will automatically increase productivity without considering the context of leadership. The application of AI needs to be carried out optimally by considering the technology's suitability for banking needs.